-9g-6g-4=-16-16g

Simple and best practice solution for -9g-6g-4=-16-16g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9g-6g-4=-16-16g equation:


Simplifying
-9g + -6g + -4 = -16 + -16g

Reorder the terms:
-4 + -9g + -6g = -16 + -16g

Combine like terms: -9g + -6g = -15g
-4 + -15g = -16 + -16g

Solving
-4 + -15g = -16 + -16g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '16g' to each side of the equation.
-4 + -15g + 16g = -16 + -16g + 16g

Combine like terms: -15g + 16g = 1g
-4 + 1g = -16 + -16g + 16g

Combine like terms: -16g + 16g = 0
-4 + 1g = -16 + 0
-4 + 1g = -16

Add '4' to each side of the equation.
-4 + 4 + 1g = -16 + 4

Combine like terms: -4 + 4 = 0
0 + 1g = -16 + 4
1g = -16 + 4

Combine like terms: -16 + 4 = -12
1g = -12

Divide each side by '1'.
g = -12

Simplifying
g = -12

See similar equations:

| -4(x-4)-6=-7+2(4-2x) | | 3x*2+6x+4800=0 | | y=-16x^2+9x+30 | | -14z+2z-7=-20-11z | | 10t=7y+15 | | 3(1-2x)=7-5x | | (2x-5)+(2x-5)+(3x-25)+(5x+45)=360 | | -6x=-2(-4+7x) | | 2x+5=135 | | 2+6y=12+7y | | -6(4k-7)-4k=-5-3(7k-4) | | 105+Y=105 | | 6y+2=-y+32 | | -9-5x=-19 | | 2(b-21)=41-3(b-4) | | (3x-7y)(x+3y)= | | 5x-3x-10=-34 | | 3x-8=-5x-20 | | -(v+4)=-4-3v | | -9+k+3k=9-2k | | 14x-21=12x+29 | | 3x+2(x+10)=170 | | N*(2n-4)=17 | | 28x+52=25 | | 3x^2+2x^2=0 | | 2(v+8)=8(-v-8) | | 5+7x=96 | | 7a+2=1 | | 1.5-.4y=3.3 | | 6x^2-44x=-63 | | -(7v+7)=5-4v | | Q+83=902 |

Equations solver categories